Effectiveness of nanomaterials and their counterparts in improving rice growth and yield under arsenic contamination - Li, Xiufen; Wang, Xiaoxuan; Ma, Xingmao; Sun, Wenjie; Chen, Kun; Dou, Fugen (Frontiers in Plant Science, 2024)
Arsenic (As) pollution in rice (Oryza sativa L.), a staple food for over 3.5 billion people, is a global problem. Mixed effects of Zn, Cu, and Si amendments on plant growth and yield, including in the presence of As pollution have been reported in previous studies. To better investigate the effectiveness of these amendments on rice growth, yield, and As accumulation, we conducted a rice greenhouse experiment with 11 treatments, including control pots with and without As contamination and pots with amendments of ZnO, CuO, and SiO2 nanoparticles (ZnO NPs, CuO NPs, and SiO2 NPs), their ionic counterparts (ZnSO4, CuSO4, and Na2SiO3), and bulk particles (ZnO BPs, CuO BPs, and SiO2 BPs). Compared with the background soil, the treatment of adding As decreased rice plant height, panicle number, and grain yield by 16.5%, 50%, and 85.7%, respectively, but significantly increased the As accumulation in milled rice grains by 3.2 times. Under As contamination, the application of Zn amendments increased rice grain yield by 4.6–7.3 times; among the three Zn amendments, ZnSO4 performed best by fully recovering grain yield to the background level and significantly reducing grain AsIII/total As ratio by 46.9%. Under As contamination, the application of Cu amendments increased grain yield by 3.8–5.6 times; all three Cu amendments significantly reduced grain AsIII/total As ratio by 20.2–65.6%. The results reveal that Zn and Cu amendments could promote rice yield and prevent As accumulation in rice grains under As contamination. Despite the observed reduction in As toxicity by the tested NPs, they do not offer more advantages over their ionic counterparts and bulk particles in promoting rice growth under As contamination. Future field research using a broader range of rice varieties, investigating various As concentrations, and encompassing diverse climate conditions will be necessary to validate our findings in achieving more extensive understanding of effective management of arsenic contaminated rice field.